2010
DOI: 10.21236/ada524439
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Civilian Casualties in Afghanistan and Iraq

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 3 publications
(9 reference statements)
3
24
0
Order By: Relevance
“…Although we show in Table 4 unreported demographic data for readers' information (civilian victims of unreported age, children of unreported sex, and in the footnote, adults of unreported sex), assessment for bias in reporting demographic information requires knowing the true demographic composition of the unknowns within this dataset, or comparison to a matched, independent dataset of comparable detail. A study using the IBC database found no media-reporting bias for governorates with higher levels of insurgent violence to have any more, or less, missing information on event location, but missing demographic information was not examined [47]. It has been established that media reports can provide systematic, meaningful data on conflict casualties [1],[7],[10],[11],[34],[48][50].…”
Section: Discussionmentioning
confidence: 99%
“…Although we show in Table 4 unreported demographic data for readers' information (civilian victims of unreported age, children of unreported sex, and in the footnote, adults of unreported sex), assessment for bias in reporting demographic information requires knowing the true demographic composition of the unknowns within this dataset, or comparison to a matched, independent dataset of comparable detail. A study using the IBC database found no media-reporting bias for governorates with higher levels of insurgent violence to have any more, or less, missing information on event location, but missing demographic information was not examined [47]. It has been established that media reports can provide systematic, meaningful data on conflict casualties [1],[7],[10],[11],[34],[48][50].…”
Section: Discussionmentioning
confidence: 99%
“…Much of this research has been done in other fields, but some recent studies in political science have explored revenge as a motive for violence in civil conflicts (Balcells 2010;Condra et al 2010). These studies, however, do not investigate cross-national variation in attitudes about revenge and instead treat revenge as a characteristic of individuals only, either as a psychological mechanism that motivates the resort to violence or else as a mobilization tool used by elites to recruit participants for violence.…”
Section: Usa-iraq India-pakistan Turkey-cyprus Venezuela-colombia Permentioning
confidence: 99%
“…As this would only give us two years of relevant data, we have chosen not to employ these data. Studies employing the data on civilian causalities include Condra et al (2010) and Berman et al (2011). The CIDNE data, leaked through WikiLeaks, list violent encounters in the period 2004 to 2009, hence partially overlapping our sample.…”
Section: A Empirical Strategy and Datamentioning
confidence: 99%